Experimental and numerical investigation on thermal management of an outdoor battery cabinet. (5th December 2015) - Meng, X.Z.; Lu, Z.; Jin, L.W.; Zhang, L.Y.; Hu, W.Y.; Wei, L.C.; Chai, J.C.
Abstract: Many forms of electronic equipment such as battery packs and telecom equipment must be stored in harsh outdoor environment. It is essential that these facilities be protected from a wide range of ambient temperatures and solar radiation. Temperature extremes greatly reduce lead-acid based battery performance and shorten battery life. Therefore, it is important to maintain the cabinet temperature within the optimal values between 20 °C and 30 °C to ensure battery stability and to extend battery lifespan. To this end, cabinet enclosures with proper thermal management have been developed to house such electronic equipment in a highly weather tight manner, especially for battery cabinet. In this paper, the flow field and temperature distribution inside an outdoor cabinet are studied experimentally and numerically. The battery cabinets house 24 batteries in two configurations namely, two-layer configuration and six-layer configuration respectively. The cabinet walls are maintained at a constant temperature by a refrigeration system. The cabinet's ability to protect the batteries from an ambient temperature as high as 50 °C is studied. An experimental facility is developed to measure the battery surface temperatures and to validate the numerical simulations. The differences between the experimental and computational fluid dynamic (CFD) results are within 5%. Highlights: Battery placement has significant effect on temperature field in battery cabinet. The six-layer configuration achieves better temperature uniformity. Internal air circulation depends on battery configuration. Natural convection could be an effective solution satisfying safety concerns.